2015
DOI: 10.1111/coep.12152
|View full text |Cite
|
Sign up to set email alerts
|

Factor Determinants of Total Factor Productivity Growth for the Japanese Manufacturing Industry

Abstract: This study uses industrial panel data for Japanese manufacturing to estimate the sources of productivity growth by simultaneously considering embodied technical progress, spillover effects, and openness, after controlling for returns to scale, imperfect competition, and capacity utilization. Estimation results show the existence of considerable embodied technical progress and interindustry externalities of capital investments positively affecting productivity growth. Furthermore, embodied technical progress ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…The positive effect of import is in line with research conducted by Negara (2016), which shows that increasing import in terms of raw materials will provide better access to foreign knowledge and technology for local industries. The positive effect of PMW is in line with research conducted by Gehringer et al (2015) and Kim (2015), which shows that an increase in PMW will have a positive effect on improving the quality of the labor force so that it may support an increase in output. Thus, an increase in LCR, total production, domestic investment, import, and PMW may…”
Section: Effect Of Local Content Requirement and Other Factors On The Manufacturing Industry Productivity Growthsupporting
confidence: 83%
“…The positive effect of import is in line with research conducted by Negara (2016), which shows that increasing import in terms of raw materials will provide better access to foreign knowledge and technology for local industries. The positive effect of PMW is in line with research conducted by Gehringer et al (2015) and Kim (2015), which shows that an increase in PMW will have a positive effect on improving the quality of the labor force so that it may support an increase in output. Thus, an increase in LCR, total production, domestic investment, import, and PMW may…”
Section: Effect Of Local Content Requirement and Other Factors On The Manufacturing Industry Productivity Growthsupporting
confidence: 83%
“…The critical question then is what is behind the slow growth that tears growth of R&D and TFP down. It is beyond the scope of this paper to give a full explanation but some of the relevant reasons may be the following: Branstetter and Nakamura (2003) defend stagnant human capital supply as a cause of stagnant R&D employment for PhD-level engineers, and Arora et al (2013) for IT software and Kim (2016) for durable manufactured goods. Arora et al (2013) argue that Japanese immigration practices are restrictive, offshoring is not used much, and domestic graduates are scarce.…”
Section: Results For Permanent Private and Public Randd Policy Changesmentioning
confidence: 99%
“…Several studies have theoretically and empirically identified factors that determine TFP (see Silveira et al 2021 for a review of literature of TFP determinants). Theory suggests that human capital (ibid; Arazmuradov et al 2014;Danska-Borsiak 2018;Akinlo and Adejumo 2016), trade (Bhattacharya et al 2021;Kim 2016), FDI/imports (Bhattacharya et al 2021;Kim 2016;Akinlo and Adejumo 2016;Harris and Moffat 2020), and R&D expenses (Danska-Borsiak 2018;Otsuka 2017;Kim 2016) are the main determinants of TFP growth. However, it is recognized that the latter is the main driver of TFP growth (among others, Saleem et al 2019;Huang et al 2019;Shabbir and Yaqoob 2019;Sharif et al 2021;Pegkas et al 2020;Tsamadias et al 2019;Haider et al 2019;Griliches 1979Griliches , 1994Griffith et al 2004;Edquist and Henrekson 2006;Hall et al 2009;Eberhardt et al 2013;Donghyun et al 2014;Gehringeer et al 2015;Venturini 2015) because it facilitates the adoption and implementation of new technologies exogenously facilitating the domestic production of technological innovations.…”
Section: The Fie Approach To Measuring Tfp Changementioning
confidence: 99%